Pengaruh Pembayaran Klaim dan Beban Operasional Terhadap Profitabilitas Perusahaan PT. Jamkrindo Cabang Makassar - Sari, Mutiara Melinda; Nasrullah, Nasrullah; Syahriati, Antenri (Universitas Teuku Umar, 2025)
This study aims to weaken the influence of claim payments and operating expenses on the profitability of PT. Jamkrindo Makassar Branch for the period 2019-2024. Using a quantitative approach with multiple linear regression techniques on secondary data from the income statement, the results of the study indicate that claim payments and operating expenses simultaneously have a significant effect on profitability. Partially, claim payments have a negative and significant effect, indicating that an increase in claim payments reduces profitability. Operating expenses also have a negative and significant effect on profitability, indicating that a large increase in operating expenses can reduce the company's profits.Keywords: Claim Payments, Operating Expenses, Profitability